The Effect of Work-From Home on Burnout during COVID-19 Disease: The Mediating Effect of Organizational and Family Support - Annisa Fajri; Haerudin Haerudin (Budapest International Research and Critics University, 2022)
Coronavirus (COVID-19), which hit in early 2020, changed the way people live and work, and affected industries and organizations all over the world. Many organizations have begun to deliver a new way of working to adapt to these shifts effectively using teleworking or a work from home policy. The purpose of this study was to fill the gaps by investigating several potential predictors of job satisfaction during working from home from the impact of COVID-19 such as work–life balance and work stress. Using a quantitative approach, 136 workers who were forced to work from home all over Indonesia participated, and the responses were analysed using PROCESS macro software. The results supported hypothesis that family support and organizational support mediate the relationship of work–life balance and burnout. It is imperative for the organizations to take substantial steps to reduce burnout on employees during COVID-19 disease, nurture decision autonomy at all levels of hierarchy and encourage amiable relationships of employees with their supervisors and peers based on mutual trust and support.